Genetic identification of hydrocarbons degrading bacteria isolated from oily sludge? and petroleum-contaminated soil in Basrah City, Iraq - ENTISAR MUHSON ABOUD; Ahmed Burghal; ABDULLAH HAMAD LAFTAH (Society for Indonesian Biodiversity, 2021)
Abstract. Aboud EM, Burghal AA, Laftah AH. 2021. Genetic identification of hydrocarbons degrading bacteria isolated from oily sludge? and petroleum-contaminated soil in Basrah City, Iraq. Biodiversitas 22: 1934-1939. Petroleum is a major problem for environmental pollution due to the extensive use, which can reach all parts of the environment. Contaminated environments are required to identify bacterial diversity that has a remarkable ability to tolerate and biodegrade toxic compounds. The process of oil degradation by microorganisms in their natural environment is affected by certain chemical, physical and biological conditions. Bioremediation techniques are powerful for removing oil pollution, which reflects the ability of microorganisms to destroy organic pollutants. In the current study, six bacterial isolates (S1-S6) were isolated from oil-contaminated soils. mineral salt medium (MSM) was used to carry out biodegradation, crude oil degradation was an evaluation by the gravimetric method. After two weeks of incubation showed S5 isolate the greatest efficiency in oil degradation 53.6%, S1 and S6 also gave good capability degradation (47.31% and 44.9%) respectively, while isolates S2 and S3 gave the lowest percentage. All isolates were identified by 16S rDNA amplicons as Pseudomonas stutzeri, Psychrobacter faecalis, Pseudomonas songnenensis, Bacillus cereus, Psychrobacter quanticus strain E9R, and Psychrobacter quanticus strain EA422 according to molecular identification. The current study indicated that hydrocarbon-degrading bacteria specially Psychrobacter can be used to clean soil from crude oil and other industrial discharges.